Hubungan Karakteristik Terhadap Kecemasan Pemberian Air Susu Ibu di UPT Puskesmas Sulili Kabupaten Pinrang - Hamdiyah; Reski Devi Akib; Nur Laela; St. Nurbaya (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Anxiety can affect bodily functions, including the production of breast milk for nursing mothers. To find out whether there is a relationship between the characteristics of the anxiety level of breastfeeding in the UPT Puskesmas Sulili, Pinrang Regency is the purpose of this study. The research method uses the type of research used is "Correlational Analytic", the research design is Cross - Sectional. The population of this study was the first day post partum mothers to the second day in the Sulili Public Health Center, Pinrang Regency as many as 37 people. Data analysis used the SPSS version 16.0 statistical test with univariate and bivariate analysis of the chi-squere method with a significance level of 0.05. The results of the research that have been presented in the form of a distribution table, then the researchers will discuss the results of the analysis based on the characteristics of education, maternal age, parity, and occupation that affect maternal anxiety in breastfeeding, namely parity and work with the value of the results of the analysis using the Chi-Squere test with a level of confidence 0.05 then obtained p value parity (0.002 > = 0.05) while the work p value parity (0.003 > = 0.05) . Further research is needed to add other factors that can affect the level of anxiety that can affect breastfeeding such as knowledge, culture, family support.